Electro convulsive therapy: knowledge and attitude among medical students (Indian Journal of Applied-Basic Medical Sciences, 2021)
Background: Electroconvulsive therapy (ECT) is a technique used to treat mental illnesses by applying electric current through the brain to induce convulsions. Stigmatized views regarding ECT also present among health care professionals which influences their decision in patient’s future treatment.Aim: to assess knowledge and attitude of medical students regarding ECT.Methods: A cross-sectional study was carried out among 180 medical students. Non-psychiatric clinician’s knowledge about and attitudes towards ECT was used to assess the association among various factors.Results: Negative attitudes like ECT causes pain to the patients (n=116), is cruel (n=40), used for punishment of violent patients(n=45) and misused by psychiatrists (n=47) were more prevalent and also significantly co-related with Unwillingness to receive ECT if indicated.Conclusion: Results of the study suggests that Most of the knowledge was obtained from mass media and rather than demonstration of ECT, hence negative attitudes were more prevalent.
Keywords: Electro convulsive therapy; knowledge; attitude; medical students; convulsive